Analisis Miskonsepsi Konsep Zat dan Karakteristiknya Pada Siswa Kelas VII di SMP Islam Bani Tamim: Analisis Miskonsepsi Konsep Zat dan Karakteristiknya Pada Siswa Kelas VII di SMP Islam Bani Tamim - Dewi Mulyani; Lukman Nulhakim; Mudmainah Vitasari (PendIPA Journal of Science Education, 2023)
The basis of the research was that misconceptions greatly affect student learning outcomes because they can understand and interpret a concept incorrectly. Students who have understood the concept can be measured from good learning outcomes. Low learning outcomes identify difficulties in the student learning process, thereby affecting the level of student understanding. The research conducted was descriptive research. The facts found from the research results were then described in accordance with the actual situation in the form of data. The data obtained was then processed, interpreted, recorded and analyzed using statistical data. In this study, researchers collected data regarding a symptom that occurs as a result of the learning process. The source of the data in this study was obtained by administering a three tier multiple choice diagnostic tests to a predetermined sample. Based on the data obtained in items 1, 7, 11 of the 18 items it is said that the highest misconception is because students cannot explain the characteristics of a solid substance correctly. Judging from these problems, students experienced misconceptions of reasoning or incomplete or incorrect reasoning. Based on the results of data analysis and discussion, it can be concluded as follows: There is a misconception about the concept of substances and their characteristics. The percentage of misconceptions about the concept of substances and their characteristics is 30%. The percentage of false negative misconceptions on the concept of substances and their characteristics is 8%. The percentage of false positive misconceptions on the concept of substances and their characteristics is 28%.